Anh văn chuyên ngành 3 - ThS. Nguyễn Thị Thu Hà (Trường Đại học Trà Vinh, 2020)
Chapter 1: The petroleum industry. Chapter 2: Energy sources. Chapter 3: The (wider) organic manufacturing industry. Chapter 4: Nitrogen. Chapter 5: Sulfur.